2023
DOI: 10.1177/03635465231161348
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcomes After Arthroscopic Treatment of Femoroacetabular Impingement for Patients With Borderline Dysplasia

Abstract: Background: Outcomes after isolated hip arthroscopic surgery for patients with dysplasia have been unfavorable. Results have included iatrogenic instability and conversion to total hip arthroplasty at a young age. However, patients with borderline dysplasia (BD) have shown more favorable results at short- and medium-term follow-up. Purpose: To assess long-term outcomes after hip arthroscopic surgery for femoroacetabular impingement in patients with BD (lateral center-edge angle [LCEA] = 18°-25°) compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Additionally, PAO has shown promise in treating patients with persistent hip instability that does not improve following single or multiple hip arthroscopic procedures 36 . Hip arthroscopy treatment patients with BDDH have durable outcomes (>9 years) and a low revision rate due to minimally invasive surgery and rapid recovery 13 . This study further demonstrated favorable outcomes for arthroscopic surgery in patients with BDDH.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Additionally, PAO has shown promise in treating patients with persistent hip instability that does not improve following single or multiple hip arthroscopic procedures 36 . Hip arthroscopy treatment patients with BDDH have durable outcomes (>9 years) and a low revision rate due to minimally invasive surgery and rapid recovery 13 . This study further demonstrated favorable outcomes for arthroscopic surgery in patients with BDDH.…”
Section: Discussionmentioning
confidence: 62%
“…Traditionally, borderline dysplasia has been defined as an acetabular LCEA between 20° to 25°. Recent studies have defined LCEA 18° to 25° as BDDH and obtained good results by arthroscopic surgery 13,14 . In severe hip dysplasia with LCEA below 18°, there is an acetabular bony structural deficiency that must be addressed, and PAO remains the gold standard to address that matter 32 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, given the relatively low number of patients who underwent revision hip arthroscopic surgery or conversion to THA, it is not yet possible to determine causative differences between patients undergoing revision hip arthroscopic surgery or conversion to THA and those who did not. The study cohort included patients with borderline hip dysplasia (ie, LCEA of 20°-25°); even though these patients have high long-term survivorship, 17,64 they may represent a different abnormality than patients without any dysplasia. Finally, the present study reports data from surgical procedures performed by a single fellowship-trained sports medicine surgeon with advanced training and experience in hip arthroscopic surgery practicing at a high-volume, tertiary referral orthopaedic practice.…”
Section: Limitationsmentioning
confidence: 99%